Alteration of the pattern of regenerative corneal subbasal nerves after laser in‐situ keratomileusis surgery. (11th August 2020) - Chao, Cecilia; Lum, Edward; Golebiowski, Blanka; Stapleton, Fiona
Abstract: Purpose: Corneal nerves exhibit high plasticity, which allows successful reinnervation after nerve damage caused by laser in‐situ keratomileusis (LASIK) surgery. This study aimed to examine corneal subbasal nerve orientation during regeneration after LASIK. Methods: This study involved 20 healthy, myopic subjects who had undergone bilateral Femto‐LASIK 12–16 months prior with a superior hinge position. The corneal subbasal nerve plexus at the central, mid‐temporal and mid‐superior cornea on the right eye were imaged using in vivo confocal microscopy. Global nerve fibre orientation (indicating the overall pattern) and variation of nerve fibre orientation (indicating the consistency of the orientation) was determined using customised MATLAB™ software (www.mathworks.com/products/matlab.html ). Differences in nerve orientation variables between groups were examined using the Mann‐Whitney U test. Linear mixed models with Bonferroni adjustment were conducted to examine differences between corneal regions, and over time, after LASIK. Results: There were no differences between post‐LASIK and control groups in global nerve orientation at any of the examined corneal regions. The post‐LASIK subjects had a greater variation of nerve orientation at the central ( p  = 0.007) and temporal ( p  = 0.049) cornea than the controls. There was a difference in global nerve fibre orientation between corneal regions ( p  < 0.001) in the controls but not in the post‐LASIK group. The variation of nerve fibre orientation was higher at the central, compared to the temporal and superior cornea after LASIK ( p  < 0.001), although there were no differences between corneal regions in controls. Conclusions: Our results demonstrate that there was an increased variability in the corneal subbasal innervation patterns following LASIK when compared to controls.